A Comparison of Alkali and Biological Pretreatment Methods in Napier Grass (Pennisetum purpureum Scumach.) for Reducing Lignin Content in the Bioethanol Production Process - T Taufikurahman; Wendo Obert Delimanto (School of Life Sciences and Technology, Institut Teknologi Bandung, 2020)
Napier grass is one of lignocellulosic plants that has the potential to be converted as bioethanol due to high productivity and relatively fast harvesting time. However, the problems of processing lignocellulosic plants into bioethanol are the high lignin content and the different lignin structure of each plant. Lignin can inhibit biological agents in accessing cellulose and hemicellulose. Therefore, it is necessary to select and optimize the pretreatment process with the aim of degrading lignin and maintaining the value of the cellulose. This study was conducted to compare the effectiveness of two different pretreatments (biological and alkaline) in degrading lignin. For the alkali pretreatment, lime (Ca(OH)2) was added to the Napier grass substrate using concentrations of 0.05, 0.1, and 0.5 grams/gram, which was then incubated at 23-25 oC each within 6, 24, and 96 hours period. For biological pretreatment, Aspergillus niger spore was used as an agent, which was incubated onto the Napier grass substrate using concentrations of 106, 107, and 108 cells/mL, an optimal temperature of 35oC and within 1, 3, 5, 7, and 9 days period. As a comparison, Phanerochaete chrysosporium was also incubated using a concentration of 106 a temperature of 35 oC within 28 days period. The extracted Napier grass was then analyzed for lignocellulose content, which included hot water soluble, Hemicellulose, cellulose, lignin, and ash, using Chesson-Datta method and reducing sugar test. Comparison of biological pretreatment between Aspergillus niger and Phanerochaete chrysosporium showed that Aspergillus niger was better at degrading lignin, with a lignin-to-cellulose ratio of 24.3%, smaller than Phanerochaete chrysosporium at 30.645%. This ratio was furthermore compared with the ratio resulting from Alkali pretreatment, which showed that the former was proven to be more optimum.